Reactive Oxygen Species, Antioxidant Responses and Implications from a Microbial Modulation Perspective - Zandi, Peiman; Schnug, Ewald (Biology (Basel, Switzerland), 2022)
Plants are exposed to various environmental stresses in their lifespan that threaten their survival. Reactive oxygen species (ROS), the byproducts of aerobic metabolism, are essential signalling molecules in regulating multiple plant developmental processes as well as in reinforcing plant tolerance to biotic and abiotic stimuli. However, intensified environmental challenges such as salinity, drought, UV irradiation, and heavy metals usually interfere with natural ROS metabolism and homeostasis, thus aggravating ROS generation excessively and ultimately resulting in oxidative stress. Cellular damage is confined to the degradation of biomolecular structures, including carbohydrates, proteins, lipids, pigments, and DNA. The nature of the double-edged function of ROS as a secondary messenger or harmful oxidant has been attributed to the degree of existing balance between cellular ROS production and ROS removal machinery. The activities of enzyme-based antioxidants, catalase (CAT, EC 1.11.1.6), monodehydroascorbate reductase (MDHAR, E.C.1.6.5.4), dehydroascorbate reductase (DHAR, EC 1.8.5.1), superoxide dismutase (SOD, EC 1.15.1.1), ascorbate peroxidase (APX, EC 1.11.1.11), glutathione reductase (GR, EC 1.6.4.2), and guaiacol peroxidase (GPX, EC 1.11.1.7); and non-enzyme based antioxidant molecules, ascorbate (AA), glutathione (GSH), carotenoids, α-tocopherol, prolines, flavonoids, and phenolics, are indeed parts of the defensive strategies developed by plants to scavenge excess ROS and to maintain cellular redox homeostasis during oxidative stress. This review briefly summarises current knowledge on enzymatic and non-enzymatic antioxidant machinery in plants. Moreover, additional information about the beneficial impact of the microbiome on countering abiotic/biotic stresses in association with roots and plant tissues has also been provided.